PERANCANGAN BANGUNAN BAGI LANSIA PENSIUNAN BEREKONOMI RENDAH DI JAKARTA BARAT - Brian Patrick; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2023)
Every human being will experience a phase of aging as well as us, from children to adults to old age is a natural process that humans experience. Elderly is a phase where humans are free from the responsibility to care for and provide for their children, whereas the elderly need care and assistance from their children and grandchildren. However, not all elderly people get the care and assistance they need and on the other hand, there are still elderly people who earn a living to meet their personal needs. There are still many elderly people who live with a low level of welfare, around 11.51% of the elderly population in Jakarta live in poverty according to BPS data in 2022. Elderly people who live within the poverty line usually find it difficult to meet their daily needs, which is caused several factors such as lack of income, and loss of income which causes a decrease in bodily functions which causes less productivity. There are also low-income elderly who receive social assistance from the government (KLJ), but can only reach the elderly who are physically and psychologically ill. Therefore, providing programs for the elderly to generate income is very important for the survival and well-being of the elderly. Empathize with creating jobs that suit the needs and abilities of the elderly and housing so that they can help the survival and welfare of the elderly, as well as commercial for the daily needs of the elderly. By applying the Healing Environment which is supported by natural, sensory, and psychological elements. Keywords: elderly; empathy; housing; income; low econom; work Abstrak Setiap manusia akan mengalami fase penuaan begitu juga dengan kita, mulai dari anak menjadi dewasa hingga menjadi tua merupakan proses alamiah yang dialami manusia. Lansia merupakan fase dimana manusia telah bebas dari tanggung jawab untuk merawat dan menafkahi anak mereka, yang sebaliknya lansia butuh perawatan dan pendampingan dari anak maupun cucu mereka. Akan tetapi, tidak semua lansia dapat perawatan dan pendampingan yang dibutuhkan dan sebaliknya masih ada lansia yang mencari nafkah untuk memenuhi kebutuhan pribadinya. Masih banyak penduduk lansia yang hidup dengan tingkat kesejahteraan yang rendah, sekitar 11,51% penduduk lansia di Jakarta yang hidup dalam kemiskinan menurut data BPS pada tahun 2022. Lansia yang hidup dalam garis kemiskinan biasanya sulit untuk memenuhi kebutuhan hidup sehari-hari, yang disebabkan beberapa faktor seperti kurangnya pendapatan, dan kehilangan pendapatan yang menyebabkan terjadinya penurunan fungsi tubuh yang menyebabkan kurang produktif. Ada pula lansia berekonomi rendah yang mendapatkan bantuan sosial dari pemerintah (KLJ), akan tetapi hanya dapat menjangkau lansia yang sakit secara fisik dan psikis. Oleh karena itu, Penyediaan program bagi lansia untuk menghasilkan pendapatan sangatlah penting untuk keberlangsungan hidup dan kesejahteraan lansia. Berempati dengan menciptakan lapangan pekerjaan yang sesuai dengan kebutuhan dan kemampuan lansia dan hunian agar dapat membantu keberlangsungan hidup dan kesejahteraan lansia, serta komersial untuk kebutuhan sehari dari lansia. Dengan mengaplikasikan Healing Environment yang didukung oleh unsur alam, indera, serta psikologis.